Training Management To Enhance Teachers' Competence: A Systematic Literature Review - Wulandari, Tyas; Rimadani, Rida; Ardianti, Vika; Yusuf Sobri, Ahmad; Fardani Ubaidillah, Aan (Proceedings Series of Educational Studies, 2024)
Abstract: Efforts to increase teacher professionalism can provide improvements in the field of education that are always implemented in order to advance the nation along with advances in science and technology. Several efforts are made to increase the competency of teaching staff through training. This is carried out to improve the quality of the nation's education and the creation of complete Indonesian people. The method used in this research is systematic literature review or SLR. The use of the SLR method aims to help unite different theoretical perspectives and in depth. A systematic literature reference search was carried out to identify relevant previous research as a review for this research. The analysis method in this article uses 2 methods, namely selecting texts that are relevant to the research objectives and the second is comparing them with best practice. In theoretical studies from several sources analyzed, it can be concluded that the training given to teachers/educators has an important role. in increasing competence and professionalism in facing future challenges. Educators are professional staff who are obliged to plan and implement the learning process, assess learning outcomes, provide guidance and training. Educators also have a professional commitment to improving the quality of education.Abstrak: Upaya peningkatan profesionalisme guru dapat memberikan perbaikan dalam bidang pendidikan yang selalu dilaksanakan dalam rangka memajukan bangsa seiring dengan kemajuan ilmu pengetahuan dan teknologi. Beberapa upaya dilakukan untuk meningkatkan kompetensi tenaga pengajar melalui pelatihan. Hal ini dilakukan untuk meningkatkan kualitas pendidikan bangsa dan terciptanya manusia Indonesia seutuhnya. Metode yang digunakan dalam penelitian ini adalah tinjauan literatur sistematik atau SLR. Penggunaan metode SLR bertujuan untuk membantu menyatukan perspektif teoritis yang berbeda dan mendalam. Pencarian referensi literatur secara sistematis dilakukan untuk mengidentifikasi penelitian terdahulu yang relevan sebagai tinjauan penelitian ini. Metode analisis pada artikel ini menggunakan 2 metode yaitu memilih teks yang relevan dengan tujuan penelitian dan kedua membandingkannya dengan best practice. Dalam kajian teori dari beberapa sumber yang dianalisis, dapat disimpulkan bahwa pelatihan yang diberikan kepada guru/pendidik mempunyai peranan penting. dalam meningkatkan kompetensi dan profesionalisme dalam menghadapi tantangan masa depan. Pendidik adalah tenaga profesional yang berkewajiban merencanakan dan melaksanakan proses pembelajaran, menilai hasil pembelajaran, memberikan bimbingan dan pelatihan. Pendidik juga mempunyai komitmen profesional dalam meningkatkan mutu pendidikan.